Study on the dynamic splitting characteristics of water-saturated red sandstone under stress waves with different pulse widths - XIE Beijing; LIN Shurong; HUANG Chunyi; LI Xiaoxu; SHI Jiayu; LUAN Zheng (矿业科学学报)
Tunnel blasting is prone to inducing disasters such as rock collapse, and parameters such as pulse width and amplitude of the blasting stress wave directly affect the degree of tensile damage of the tunnel surrounding rock. In order to investigate and quantitatively analyse the effects of pulse width and amplitude on the dynamic mechanical properties of water-saturated red sandstone, a dynamic Brazilian splitting test was carried out on dry/water-saturated red sandstone by using a split Hopkinson pressure bar system, a high-speed video camera, and digital imaging technology. The results show that the water-saturated condition can weaken the strength of red sandstone, with tensile strength weakening rates of 91.16 %, 94.00 %, 94.86 % and 95.09 % for bullet impacts of 200 mm, 300 mm, 400 mm and 500 mm length, respectively; the damage mode of red sandstone is dominated by the expansion of tensile cracks, and the increase of the pulse width of the incident stress wave can promote the initiation and expansion of tensile cracks; moisture inhibits the absorption of energy in red sandstone, and the absorbed energy per unit volume increases with the increase of the pulse width of the stress wave; the percentage of non-tensile energy consumption of water-saturated red sandstone is higher than 80 % under the conditions of impact speed greater than 8 m/s under each pulse width, and the energy consumption rate of red sandstone decreases to less than 5 % when the impact speed is greater than 10 m/s, and the free water in cracks can produce a force that can inhibit the expansion of cracks, and the absorbed energy is used for shear damage.